STUDI EKSPERIMENTAL PEMBANGKITAN GAYA MAGNETIK PADA KUMPARAN BERARUS DALAM MEDAN MAGNET NEODYMIUM - Wandi Arnandi; Sigit Iswahyudi (Wahana Ilmuwan, 2017)
This research is a preliminary study to develop a magnetic force generator as a thrush force of vehicle. The purpose is to investigate the effect of electric current and coil diameter on the generation of magnetic force of current-carrying coilconductor in magnetic field of neodymium magnet. To reach the goal, a magnetic circuit and three coil which havea difference of coil diameter were made and tested. The coilswere made of laminated copper wirewhich have 1,1 mm in diameter and 3000 mm length. The coil diameter was varied 35 mm, 38 mm, and 50 mm. The source of magnetomotive force in the magnetic circuit was cylindrical neodymium magnet.The source of dc current was power supply which can produce 30 ampere of output dc current and output voltage that can be varied. The electric current in the coil was set up 1,0 ampere; 2,0 ampere; 3,0 ampere; 4,0 ampere; 5,0 ampere; 6,0 ampere; and 7,0 ampere. Testing was carried out by flowing current in the coil which placed in the magnetic flux of magnetic circuit and then magnetic force produced by the coil was measured using spring scale in unit of Newton. Result shows that the magnitude of magnetic force produced by thecoil is directly proportional tothe magnitude of electric current and coil diameter.